Influence of fabrication processing on perovskite phase formation of KNN-BZT - Sutapun M. (2014)
The binary system of (1-x)(K1/2Na1/2)NbO 3-xBi(Zni/2Ti1/2)O3; x = 0.0-0.30 ceramics was fabricated by conventionally mixed oxide and two-stage mixed oxide methods. Phase development of calcined powders and the crystal structure of sintered ceramics were analyzed by X-ray diffraction (XRD). The microstructure analyses were undertaken by scanning electron microscopy (SEM). In the conventional method, the perovskite phases were obtained for compositions containing only 10 mol % KNN. For compositions above this amount, a complex mixture of phases was observed. However, the complete solid solution of perovskite phase, prepared by two-stage mixed oxide, was retained up to 20 mole % BZT content. The experiments in this study suggest that the two-stage mixed oxide method helps to stabilize the perovskite phase better, when compared with the conventional method. © 2008 Trans Tech Publications, Switzerland.